A novel approach for nondestructive depth-resolved analysis of residual stress and grain interaction in the near-surface zone applied to an austenitic stainless steel sample subjected to mechanical polishing. (15th May 2022) - Marciszko-Wiąckowska, M.; Oponowicz, A.; Baczmański, A.; Braham, Ch.; Wątroba, M.; Wróbel, M.; Klaus, M.; Genzel, Ch.
Graphical abstract: Highlights: Grain interaction model – the critical element of correct residual stress analysis. New tunable free surface model for in-depth residual stress determination. Nondestructive X-ray diffraction for stress gradient determination up to 60 µm. Abstract: The choice of the grain interaction model is a critical element of residual stress analysis using diffraction methods. For the near-surface region of a mechanically polished austenitic steel, it is shown that the application of the widely used Eshelby-Kröner model does not lead to a satisfactory agreement with experimental observations. Therefore, a new grain interaction model called 'tunable free-surface' is proposed, allowing for the determination of the in-depth evolution of the elastic interaction between grains. It has a strong physical justification and is adjusted to experimental data using three complementary verification methods. It is shown that a significant relaxation of the intergranular stresses perpendicular to the sample surface occurs in the subsurface layer having a thickness comparable with the average size of the grain. Using the new type of X-ray Stress Factors, the in-depth evolution (up to the depth of 45 μm) of residual stresses and of the strain-free lattice parameter is determined.